ä¸¹å¤§å¦ç”Ÿå¯¹æ ¸å¿ƒç¦»åˆè¯ä½¿ç”¨åè¯¯åˆ†æž - Harnita, Dian; Thamrin, Lily; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
As for a Chinese language learners , central separable words is not only the key point in Chinese language teaching for foreigners, also one of the difficult subjects for learners to study on. For this reason, the research was conducted for Chinese language learners, especially the student of Chinese Language Departement at Tanjungpura University, Pedagogical Institute, to make students be more proficient with mastering the grammar of Chinese language. For achieving this objective, the Author surveyed third year students at Tanjungpura University for mistakes made while use of central separable words in Chinese, summerize commonly seen types of mistakes, investigate the causes of errors, and after that confront with them to raise countermeasures. Hopefully this work help Chinese language learners to make a step further for better understanding the use of separable words, thus reduce confusions and mistakes on separable words usage. Key Words: Tanjungpura Universityâ€™s third year students, Central SeparableWords, Error Analysisæ‘˜è¦ï¼šå¯¹äºŽæ±‰è¯å¦ä¹ è€…è€Œè¨€ï¼Œæ ¸å¿ƒç¦»åˆè¯ä¸ä»…æ˜¯ä¸€ä¸ªè¯æ³•é‡ç‚¹ï¼Œä¹Ÿæ˜¯å¦ä¹ æ±‰è¯çš„éš¾ç‚¹ä¹‹ä¸€ã€‚ä¸ºæ¤ï¼Œæœ¬ç ”ç©¶çš„ç›®çš„æ˜¯ä¸ºäº†ä½¿æ±‰è¯å¦ä¹ è€…ï¼Œå°¤å…¶æ˜¯ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢ä¸æ–‡ç³»çš„å¦ç”Ÿèƒ½å¤Ÿæ›´å¿«æ›´å¥½åœ°æŽŒæ¡æ±‰è¯æ ¸å¿ƒç¦»åˆè¯çš„ç”¨æ³•ï¼Œä»Žè€Œä½¿å¦ç”Ÿèƒ½å¤Ÿæ›´ä¸ºç†Ÿç»ƒåœ°æŽŒæ¡æ±‰è¯è¯æ³•ã€‚ä¸ºäº†è¾¾åˆ°è¿™ä¸€ç›®æ ‡ï¼Œç¬”è€…è°ƒæŸ¥ä¸¹å¤§å¤§ä¸‰å¦ç”Ÿåœ¨ä½¿ç”¨æ±‰è¯æ ¸å¿ƒç¦»åˆè¯æ—¶æ‰€å‡ºçŽ°çš„ä¸€äº›åè¯¯ï¼Œæ€»ç»“å‡ºå¸¸è§çš„åè¯¯ç±»åž‹ï¼Œå¹¶æŽ¢æ±‚å‡ºçŽ°è¿™äº›åè¯¯çš„åŽŸå› ï¼Œè¿›è€Œé’ˆå¯¹è¿™äº›é—®é¢˜æå‡ºå‡ ç‚¹æ•™å¦å¯¹ç–ã€‚å¸Œæœ›æœ‰åŠ©äºŽæ±‰è¯å¦ä¹ è€…è¿›ä¸€æ¥äº†è§£æ±‰è¯ç¦»åˆè¯çš„ç”¨æ³•ï¼Œä»Žè€Œå‡å°‘ç¦»åˆè¯çš„æ··ç”¨å’Œé”™ç”¨çŽ°è±¡ã€‚å…³é”®è¯ï¼šä¸¹å¤§å¤§ä¸‰å¦ç”Ÿï¼Œæ ¸å¿ƒç¦»åˆè¯ï¼Œåè¯¯åˆ†æž